Penanganan Lingkungan Fisik Di Objek Wisata Air Panas Desa Mengeruda, Kabupaten Ngada, Provinsi Nusa Tenggara Timur - Desi Deratus Adven Meo; Ida Bagus Suryawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2018)
The tourism object of Mengeruda hot spring which located in Mengeruda village, Soa sub-district, Ngada regency is set as “Tourism Object” based on the decision letter of Ngada Regent no 7, year 2000. Besides that, the tourism object of Mengeruda hot spring have other attractions such as beautiful natural environment, but not supported by good physical environment condition, so it is necessary to make efforts or optimize the arrangement of the physical environment in the tourism object of Mengeruda hot spring. In this research used qualitative research methods. Data collected through observation in the field or observation to know the actual condition picture related to physical environment and also interview to know the effort or optimization of arrangement of physical environment of hot water recreation object. Data were analyzed using descriptive method. The results of this study describe the physical environment conditions both natural and artificial experiencing problems that require serious action and handling to improve the quality of the tourism object of Mengeruda hot spring. Existing problems show the tourism object of Mengeruda hot spring requires optimization of the arrangement of the physical environment according to existing planning. Keywords : Tourism Object, Physical Environment, Optimization